Dira lues Das Seuchenmotiv in der lateinischen Dichtung des ersten vor- und nachchristlichen Jahrhunderts - Neuwahl, Fabian (Wissenschaftliche Buchgesellschaft (wbg), 2022)
The epidemic motif stretches from the first century BC to the first century AD with remarkable continuity and thus forms an exceptional example of the principle of aemulation in ancient poetry. Fabian Neuwahl brings together for the first time the entire Latin motif tradition and offers an annotated translation.